Traditional Shalish system for rural dispute resolution in Bangladesh: An analytical study of its structure and operational mechanism - Hoque, Muhammad Rafiqul; Zarif, Muhammad Mustaqim Mohd (IIUC Studies, 2020)
This study aims at exploring the structure and operational mechanism of Shalish-a traditional rural dispute resolution system in Bangladesh. It seems that this dispute resolution system, being very informal and flexible in nature, has no organized structure and operational mechanism. However, this paper aims to critically investigate the situation. Based on observation of a number of Shalish events in a rural area of the country and extensive discussion with some Shalishkars and disputants, this qualitative study finds that the system is well structured and its operational mechanism is quite effective, albeit with some limitations. It is recommended that a local Alim (Islamic Scholar) should be included in all Shalish to ensure shari’ah related issues like some family and inheritance related disputes. Shalishkars need to be trained and upgraded in their experiences and qualities through workshops, seminars in respect of legal, moral and shari’a issues. IIUC Studies Vol.16, December 2019: 35-56